2022
DOI: 10.1021/acscatal.2c01897
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow-Temperature NOx Reduction over SmMn2O5 Mullite Catalysts Via Modulating the Superficial Dual-Functional Active Sites

Abstract: The development of highly efficient catalysts for low-temperature NO x abatement still existed as a scabrous issue. An acid-etched mullite-type SmMn2O5 catalyst (SM-E) was developed and applied in ultralow-temperature selective catalytic reduction of NO x with NH3 (NH3-SCR) to meet the increasingly rigorous demands of emission control in the nonelectric industry, which can convert more than 90% NO x in a wide operating window (90–200 °C). It has been demonstrated that NO can be preferably adsorbed and activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 74 publications
(139 reference statements)
1
21
0
Order By: Relevance
“…Mn 3+ is suggested to be the ozone decomposition site. Equally, since the ozonation of benzene at RT obeys the Langmuir–Hinshelwood model, ,, the adsorption and oxidation of benzene on the acid sites of the YMO surface need to be considered. Recent studies have shown that Lewis acid sites play a more critical role in VOC ozonation reactions. , In mullite-type manganese oxides, Mn 4+ centered in octahedron empty states (e.g., orbitals) are located above the Fermi level .…”
Section: Resultsmentioning
confidence: 99%
“…Mn 3+ is suggested to be the ozone decomposition site. Equally, since the ozonation of benzene at RT obeys the Langmuir–Hinshelwood model, ,, the adsorption and oxidation of benzene on the acid sites of the YMO surface need to be considered. Recent studies have shown that Lewis acid sites play a more critical role in VOC ozonation reactions. , In mullite-type manganese oxides, Mn 4+ centered in octahedron empty states (e.g., orbitals) are located above the Fermi level .…”
Section: Resultsmentioning
confidence: 99%
“…As shown in surface of the mullite catalyst is composed of a Mn central octahedron and pyramid ligand alternately, which will facilitate the activation of surface oxygen and lattice oxygen, thus improving the catalytic performance. 24 Although there are differences in the shape of each catalyst on the XRD pattern, all AMn 2 O 5 samples show typical diffraction characteristics of the mullite phase (121, 211, 130, 212 Miller index crystal planes), which further indicates the successful synthesis of five Mnbased mullite catalysts (Figure 5). In addition, any other diffraction peaks from the individual oxide components were not detected, especially the MnO 2 heterophase, which is prone to occur at high-temperature calcination during catalyst synthesis (dashed box in Figure 5).…”
Section: The Journal Of Physicalmentioning
confidence: 90%
“…As shown in Figure 2b, the 150, 278, 336, 413, 557, 648, and 787 cm −1 bands observed at ZrTi-C calcinated at 800 °C are attributed to crystalline ZrTiO 4 , 33,34 and most of these peaks disappear after being supported with Mn oxides, leaving only the Zr−O bond (278 cm −1 ) 35 with emerged peaks at 590 and 634 cm −1 attributed to the Mn−O bending mode. 11,36,37 Similar to the XRD results, there are not any bands corresponding to crystalline anatase or monoclinic zirconia in the Raman spectrum of ZrTi-A, while peaks at 139, 271, and 593 cm −1 corresponding to Ti−O, Zr−O, and Mn−O appear after loading with manganese oxide, 38 indicating that the addition of Mn active species tends to break the amorphous state of the ZrTi-A surface, forming bonds with Ti or Zr through O connection. Besides, it is found that only one peak corresponding to the Mn−O bond appears around 593 cm −1 on Mn/ZrTi-A; however, two peaks of 590 and 634 cm −1 corresponding to Mn−O bonds arise in the Raman spectra of Mn/ZrTi-C.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…To date, some transition-metal oxides and zeolite catalysts have been explored for their low-temperature catalytic performance, , among which Mn-based oxides have acquired more tremendous attention due to their super redox capacity. Liu et al constructed MnO 2 nanosheets with large oxygen vacancies which achieved 100% NO conversion at 100 °C . However, N 2 selectivity is an inescapable problem for the commercial applications of an Mn-based catalyst. Due to the intrinsic cause of the confining void environment and the site-specific selectivity of Mn oxides, Song et al located Mn oxides in microporous TiO 2 with small pores of molecular dimensions and found that the catalyst exhibited superior N 2 selectivity with more than 98% at 100–200 °C .…”
Section: Introductionmentioning
confidence: 99%